Performance evaluation of a wire mesh wheel on deformable terrains. (December 2016) - Huang, Han; Li, Jianqiao; Chen, Baichao; Wu, Baoguang; Zou, Meng
Highlights: The pressure-sinkage characteristic of a Wire Mesh Wheel (WMW) was contrasted. A novel pressure-sinkage model for the WCW was presented. Non-contact measurement on rut of the WMW was conduct. The contrastive analysis on traction performance of the WMW and CW was conducted. Abstract: Because of the unique lunar environment, a suitable wheel for lunar rover decides the rover's trafficability on deformable terrains. The wire mesh wheel (hereinafter referred to as WMW) has the advantages of light weight and superior stability, been widely adopted for lunar rovers. But a comprehensive research on performance of WMW on deformable terrains has not been conduct. This paper would provide particular study on a type WMW, including quasi-static pressure-sinkage test and driving performance. A novel pressure-sinkage model for the WMW on deformable soils was presented. In order to investigate the sinkage characteristics of the WMW, tests were performed using a single-wheel testbed for the WMW with different loads and velocities. The effects of load and velocity on sinkage were analyzed, and the relationship between real and apparent sinkage was presented. The research on traction performance of WMW under different slip ratios (0.1–0.6) was also conducted, contrast tests were proceed by using a normal cylindrical wheel (hereinafter referred to as CW). The traction performance of WMW is analyzed using performance indices including wheel sinkage, drawbar pull, driving torque, and tractive efficiency. The experimental results and conclusions are useful for optimal WMW design and improvement/verification of wheel–soil interaction mechanics model.